About retail price of electricity - Дорошенко, Олександр Іванович; Борисенко, Світлана Олександрівна (Technology audit and production reserves, 2015)
Based on the physics of the normal operation of electrical power systems, the paper proposes a new methodological approach to the definition of retail electricity prices for industrial and equated to them users, which considers the electrical network of electrical power systems with a rated voltage of 110 kV as the counter of the energy market of Ukraine, from which power supplier supply to consumers the electric voltage that is seen as a potential condition of electricity, which is transformed by the receivers of electricity consumers in other types of electrokinetic energy to perform useful work. The algorithms for determination of the retail price of electricity are proposed to specific consumers based on concepts and nominal voltage of their power at guideline value of reactive power factor of electricity transmission, the value of which is set at the state level and has a value of 0,25 r. u. It is argued that the practice of calculating the fees of consumers for active and reactive energy, which exists in our time due to the fact that at the state level, there are regulations that require such fee, that neither theoretically nor practically not possible due to the fact that reactive power, as a separate commercial products does not exist. Obviously, such practice is contrary to the moral and legal standards and must be stopped.